Spatial localization during open-loop smooth pursuit - Dowiasch, Stefan; Blanke, Marius; Knöll, Jonas; Bremmer, Frank (Frontiers in Neuroscience, 2023)
Numerous previous studies have shown that eye movements induce errors in the localization of briefly flashed stimuli. Remarkably, the error pattern is indicative of the underlying eye movement and the exact experimental condition. For smooth pursuit eye movements (SPEM) and the slow phase of the optokinetic nystagmus (OKN), perceived stimulus locations are shifted in the direction of the ongoing eye movement, with a hemifield asymmetry observed only during SPEM. During the slow phases of the optokinetic afternystagmus (OKAN), however, the error pattern can be described as a perceptual expansion of space. Different from SPEM and OKN, the OKAN is an open-loop eye movement. Visually guided smooth pursuit can be transformed into an open-loop eye movement by briefly blanking the pursuit target (gap). Here, we examined flash localization during open-loop pursuit and asked, whether localization is also prone to errors and whether these are similar to those found during SPEM or during OKAN. Human subjects tracked a pursuit target. In half of the trials, the target was extinguished for 300 ms (gap) during the steady-state, inducing open-loop pursuit. Flashes were presented during this gap or during steady-state (closed-loop) pursuit. In both conditions, perceived flash locations were shifted in the direction of the eye movement. The overall error pattern was very similar with error size being slightly smaller in the gap condition. The differences between errors in the open- and closed-loop conditions were largest in the central visual field and smallest in the periphery. We discuss the findings in light of the neural substrates driving the different forms of eye movements.